The Implications of BMT Financing on MSMEs Development - Shafrani, Yoiz Shofwa; Rahmini Hadi (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2023)
The capital problem faced by MSME businessmen is the difficulty in reaching banks due to the inability to provide bankable requirements. BMT aims to develop productive businesses and invest in improving the quality of economic activity in the real sector, especially micro, small, and medium entrepreneurs. BMT in Banyumas Regency helps members overcome capital problems through a variety of products. This study aims to find out how MSMEs develop after getting financing from BMT in Banyumas Regency. Therefore, this study uses a quantitative approach with 150 samples and the Wilcoxon Signed Rank Test ( two related samples test) as a tool. The results of the data analysis show that there is a significant difference between before and after the provision of financing on indicators of capital, sales turnover, income/profit, number of customers, and number of workers. Then, the results of the different tests show that the provision of financing is considered effective because it has given different results in a positive direction after the provision of financing. Except for the number of workers, the results of the analysis show that half of the sample shows no increase in the use of the number of workers.